2020
DOI: 10.3390/molecules25163590
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Multi-Residue Detection Methods for Pesticides and Veterinary Drugs

Abstract: The excessive use or abuse of pesticides and veterinary drugs leads to residues in food, which can threaten human health. Therefore, there is an extremely urgent need for multi-analyte analysis techniques for the detection of pesticide and veterinary drug residues, which can be applied as screening techniques for food safety monitoring and detection. Recent developments related to rapid multi-residue detection methods for pesticide and veterinary drug residues are reviewed herein. Methods based on different re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 120 publications
0
16
0
Order By: Relevance
“…Polyclonal, monoclonal and recombinant antibodies have been frequently used for insecticide detection. Due to the very high equilibrium association constants, these antibodies can recognize antigens sensitively [ 92 , 93 ]. With the development of nanomaterials and nanotechnology, new and wide opportunities have been brought in the development of optical immunosensors with this recognition element.…”
Section: Recognition Elementsmentioning
confidence: 99%
“…Polyclonal, monoclonal and recombinant antibodies have been frequently used for insecticide detection. Due to the very high equilibrium association constants, these antibodies can recognize antigens sensitively [ 92 , 93 ]. With the development of nanomaterials and nanotechnology, new and wide opportunities have been brought in the development of optical immunosensors with this recognition element.…”
Section: Recognition Elementsmentioning
confidence: 99%
“…With the continuous improvement of SERS for over 40 years, SERS-active materials have been redesigned from transition and noble metals into semiconductor materials with improved stability, photoluminescence, band gap, and resistance to degradation [71]. Recently, it was observed that semiconductors (TiO 2 and CdTe) could afford higher enhancement (>10 6 ) under optimized conditions [72,73]. Moreover, traditional SERS substrates have been transformed from rigid to flexible materials, such as cellulose paper, in which noble metal nanoparticles are decorated onto flexible frameworks to render the substrates inexpensive, flexible, and portable [74].…”
Section: Surface-enhanced Raman Spectroscopy and Its Application In The Analyses Of Pesticides And Veterinary Drugsmentioning
confidence: 99%
“…Ideally, pesticides and veterinary drugs should be specifically fatal to the targeted microorganism, but harmless to non-targeted animals and humans [4]. However, indiscriminate application of pesticides and veterinary drugs leaves unwanted residues in foods and the environment [5,6]. Moreover, the excessive application of these chemicals under the assumption, "if little is good, a lot more will be better," has worsened the situation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Pesticides are particularly important among agrochemicals as they are widely used in modern agriculture to control weeds and different pests affecting crops [ 1 , 2 ]. They play an important role in improving agricultural production providing important benefits for humanity.…”
Section: Introductionmentioning
confidence: 99%